Identificação de indivíduos vulneráveis no entorno de um hospital universitário: conectando vulnerabilidade, solidariedade e saúde - Hellen Cristina Sthal (Ciência & Saúde Coletiva, 2011)
In the area around a university hospital in the interior of São Paulo state people are found sleeping, eating or resting on the lawns and surrounding areas, and they linger in such sites for hours. This study sought to identify and characterize vulnerable individuals in the area around the hospital by offering help. Data were collected from November 2007 to October 2008, on a weekly basis and on randomly selected days and times. The people found in these places were identified, and 52 subjects were interviewed. The individuals were, predominantly, females (67.3%), white (51.9%), married (59.6%), had attended school for up to four years (44.2%) and did not have a defined profession (84.6%). Most of them were waiting for bus transportation provided by their hometown administration; the mean waiting time was approximately 90 minutes and most of the subjects had certain needs during the waiting period. Help was offered to 15 individuals who reported specific needs at the moment of the interview. It was concluded that these individuals were in a situation of individual, social and systematic vulnerability, especially in terms of socio-economic vulnerability. They showed reduced self-determination ability and submitted themselves to unfavorable conditions due to their dependence on public services.